Inflammatory myofibroblastic tumor of carotid artery resulting in recurrent syncope: A case report. Issue 7 (29th March 2016) - Yang, Liu; Li, Wen; Zhang, Hongying
Abstract: Background: Inflammatory myofibroblastic tumor rarely occurs in the carotid artery, whereas syncope is infrequently associated with neck mass. Methods and Results: We reby present a case in which a 56‐year‐old man with inflammatory myofibroblastic tumor at the left carotid bifurcation and is accompanied by recurrent syncope and falls. He underwent surgery, after which corticosteroids and antibiotics were administered for a short term. No recurrence was observed during the 2‐year follow‐up. Conclusion: To our knowledge, this is the first case of inflammatory myofibroblastic tumor in which recurrent syncope is the only clinical manifestation. © 2016 Wiley Periodicals, Inc. Head Neck 38: E2461–E2463, 2016